Desenvolvimento de um amostrador passivo para determinação de hidrocarbonetos policíclicos aromáticos e seus derivados nitrados e oxigenados em água por GCxGC/QTOFMS/M - Nathan de Souza Coelho (2023)
Polycyclic aromatic hydrocarbons (PAHs), as well as their nitrated (nitro-PAHs) and oxygenated (oxi-PAHs) derivatives, are widely studied substances due to their harmful health effects. They are broadly distributed in aquatic environments as a complex mixture and are quite persistent due to their low solubility. Miniaturized passive sampling techniques are ideal for environmental monitoring of these compounds, as they are more sensitive to temporal variations of target pollutant levels compared to traditional sampling methods and require small amounts of material to provide statistically significant information. This study presents the development of a new extraction fiber, using polydimethylsiloxane (PDMS) as the extracting phase, for a passive sampling device for PAHs and derivative analysis in water. The research focused on the analysis of the passive sampling capture profile in the equilibrium region, examining the characteristics and patterns of this specific area. The fiber was characterized by thermogravimetric analysis (TG and DTG), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM), confirming the presence of PDMS. A new separation and determination method for 16 PAHs, 4 nitro-PAHs, and 4 oxi-PAHs was validated using GCxGC/Q-TOFMS/MS. The results showed that the evaluated figures of merit were adequate for environmental analysis of PAHs and derivatives. The determination coefficients found were above 0.90; the detection (LOD) and quantification (LOQ) limits ranged from 0.07 ng L-1 to 1.50 ng L-1 and 0.33 ng L-1 to 6.65 ng L-1, respectively; recovery ranged between 72% and 117%; and intra and interday precision varying from 1% to 20%. Samplers were calibrated in the lab, with exposure times for analysis in the equilibrium region ranging from 3 to 10 days and sampling rates from 1.05 mL d-1 to 7.85 mL d-1. The partition coefficients between PDMS and water were also evaluated, presenting logarithm values ranging from 2.78 to 5.98. The fibers were applied in the analysis of real water samples, demonstrating high capacity. The passive sampling devices (PSD) will still be verified in loco. It is noteworthy that the presented procedure is innovative in relation to the determination of PAHs and derivatives in water.